An Analysis of the Effectiveness of a Reading Program to Improve Literacy Skills of Grade II Students at SDN 15 Koto Baru - Ahmad Ilham Asmaryadi; Nanik Setiawati; Karlina Karlina (The Future of Education Journal, 2025)
This study aims to evaluate the effectiveness of a reading program implemented in Grade II of elementary school in improving students’ literacy skills. A qualitative research method with a case study approach was used, involving one Grade II teacher and several students as participants. Data were collected through observations, interviews, and documentation, and analyzed using descriptive qualitative techniques. The results show that the reading program is effective in enhancing students' literacy skills. It helps students recognize letters, expand vocabulary, and understand sentence structure. Activities such as name-building through puzzle games and singing the alphabet song increased student engagement and motivation. In addition, the program also strengthens listening skills, improves the ability to follow instructions, and trains students’ focus. However, challenges such as limited time and students’ short attention spans need to be addressed. Time constraints hinder the consistent implementation of the program, while limited focus affects the effectiveness of the activities. Therefore, it is recommended to optimize time management and apply strategies that help maintain students’ attention throughout the learning process.